“In Parents’ School Experience, the Teacher was just Lecturing at the Front”: School-Family Partnerships in Schools with Personalized Learning Concepts - Vasarik Staub, Katriina; Stebler, Rita; Reusser, Kurt (International Journal about Parents in Education, 2023)
Our study examines communication and cooperation between schools that have implemented personalized learning concepts and the families of their students. The study forms part of a longitudinal mixed-methods research project (2012–2015, supported by the foundation Mercator Switzerland). Conducting a qualitative content analysis of interviews and strategic documents (N = 12 schools), we developed an analytic instrument, applying a semi-deductive procedure. It is based on research on school-family partnerships and consists of five communication and cooperation structures (a) channels of two-way information exchange and cooperation; b) information flow from schools to parents; c) parent events; d) parent volunteering; e) parent involvement in decision-making) and five content and object areas i) psychological, pedagogical, and school concepts; ii) understanding families; iii) learning and instruction; iv) learning progress and achievement; v) problems, conflicts). The linkage between the structures and the content of the interactions led to three paradigmatic types of schools. Type 1: Informal communication and cooperation; Type 2: Reactive communication and cooperation; Type 3: Strategic communication and cooperation. The results indicate that it can be particularly advantageous to center the communication on student progress, to focus parent events on education-related topics, and to give the parents a voice in decision-making processes.